Adaptation as a part of system resilience. insights from fish producers organizations in Portugal - Karadzic, Vanja (2014)
Complex problems of globalized society challenge its adaptive capacity. However, it is precisely the nature of these human induced problems that provide enough evidence to show that adaptability may not be on a resilient path. This thesis explores the ambiguity of the idea of adaptation (and its practice) and illustrates the ways in which adaptability contributes to resilience of social ecological systems. The thesis combines a case study and grounded theory approach and develops an analytical framework to study adaptability in resource users’ organizations: from what it depends on and what the key challenges are for resource management and system resilience. It does so for the specific case of fish producers’ organizations (POs) in Portugal. The findings suggest that while ecological and market context, including the type of crisis, may influence the character of fishers’ adaptation within POs (i.e. anticipatory, maladaptive and reactively adaptive), it does not determine it. Instead, it makes agency even more crucial (i.e. leadership, trust and agent’s perceptions in terms of their impact on fishers’ motivation to learn from each other). In sum, it was found that internal adaptation can improve POs’ contribution to fishery management and resilience, but it is not a panacea and may, in some cases, increase system vulnerability to change. Continuous maladaptation of some Portuguese POs points at a basic institutional problem (fish market regime), which clearly reduces fisheries resilience as it promotes overfishing. However, structural change may not be sufficient to address other barriers to Portuguese fishers’ (PO members) adaptability, such as history (collective memory) and associated problematic self-perceptions. The agency (people involved in structures and practices) also needs to change. What and how institutional change and agency change build on one another (e.g. comparison of fisheries governance in Portugal and other EU countries) is a topic to be explored in further research.